Modalidad híbrida y su implementación en el proceso enseñanza – aprendizaje en los estudiantes de bachillerato de la unidad educativa “Soldado Monge”, cantón El Empalme, periodo 2021-2022 - Plaza Ormaza, Galo Ramón (2023)
The confinement due to covid-19 considerably affected the educational system, presenting changes in the ways of teaching - learning, as well as the partial or total closure of schools around the world, which forced the implementation of training plans. and communication between teachers and students and the incorporation of new modalities of study, in such a way that the traditional form of study was left aside.The objective of the development project is; to analyze the hybrid modality and its implementation in the teaching-learning process in high school students of the "Soldado Monge" Educational Unit, Cantón El Empalme, period 2021-2022. A type of bibliographic field research was designed with the qualitative-quantitative, descriptive and exploratory method, with the use of instruments such as observation, surveys and interviews.It is concluded that the hybrid modality, given its flexibility, allows the integration of new digital tools and didactic practices in classes, promoting autonomous and meaningful learning in students. On the other hand, a training plan was developed for the teachers of the aforementioned educational unit, in order to enhance their skills in the implementation of the hybrid modality.